Engineered exosomes with RNA ‐motif short hairpin RNA loading and Rab4‐boosted production enable controlled ferroptosis in endometrial carcinoma - Jiarui Zhang; Yuwei Yao; Wan Shu; Shuangshuang Cheng; Guanglei Zhong; Jia Yu; Jinhua Chen; Kejun Dong; Yingying Peng; Jun Zhang; Hongbo Wang (Bioengineering & Translational Medicine, 2026)
Abstract Therapeutic challenges in endometrial carcinoma (EC) arise from the limited efficacy and toxicity of current treatments. Although exosome‐based RNA interference shows promise, its clinical translation is hindered by inefficient cargo loading, low yields, and poor tumor targeting. We have engineered an exosome platform (cRGD‐ExoM) that integrates the following innovations: Firstly, RNA motifs enable the enrichment of shRNA loading by over 80‐fold for targeting of ferroptosis regulators (glutathione peroxidase 4/ferroptosis suppressor protein 1/ferritin heavy chain [GPX4/FSP1/FTH]). Secondly, Rab4 silencing amplifies exosome biogenesis via dysregulated endosomal recycling, enhancing tumor cell uptake by impairing endosome maturation—a dual‐action mechanism that boosts both production and delivery. Thirdly, cRGD peptides confer αvβ3‐integrin‐specific targeting. cRGD‐ExoM induces potent ferroptosis by increasing lipid peroxidation and downregulating GPX4/FSP1/FTH, significantly suppressing EC tumor growth in vivo without causing systemic toxicity. The platform's modular design allows for spatiotemporal control of loading, production, and targeting, demonstrating its scalability. This study provides new insights into the precision treatment of endometrial cancer by developing engineered, multifunctional, exosome‐based therapeutic drugs that combine mechanism precision and translational feasibility in tumor treatment.